Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M; Royo, A; Gil, L; Pardos, J A (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)

Effect of nursery location and outplanting date on field performance of Pinus halepensis and Quercus ilex seedlings - Pardos, M.; Royo, A.; Gil, L.; Pardos, J. A. (Forestry, 2003)
One-year-old seedlings of Aleppo pine (Pinus halepensis Mill.) and holm oak (Quercus ilex L.) were over-wintered in the nursery under two contrasting conditions (greenhouse vs outdoors), which were chosen to simulate coastal vs inland thermal regimes. Seedling morphology, root growth potential (RGP) and shoot cold hardiness were assessed at lifting (at monthly intervals from November to March), and related to survival and field performance during two growing seasons. At lifting, behaviour outdoors was similar in both species. Conversely, the milder conditions in the greenhouse affected nursery performance in Aleppo pine seedlings (shoot growth during winter, low cold hardiness, low RGP), and influenced field performance negatively. Thus, nursery thermal regime had a significant effect on survival of outplanted Aleppo pine seedlings, and autumn outplanting appears to be the preferred option for this species. This issue does not seem as relevant in holm oak, a species less sensitive to frost. Minimum field temperatures in the 3 weeks around outplanting date were a critical acclimation period for Aleppo pine seedlings. Higher RGP at lifting was related to higher survival in Aleppo pine and taller holm oak seedlings. There was also a significant correlation between mortality after outplanting and foliar electrolyte leakage in Aleppo pine. Thus, cold hardiness is a good physiological indicator for determining the best lifting and planting dates in Aleppo pine, and RGP shows more promise for assessing holm oak vitality.
10.1093/forestry/76.1.6710.1093/forestry/76.1.67
Keywords: nursery location; outplanting; Pinus halepensis; Quercus ilex; Root growth; seedlings; shoot growth; survival (voyant)